Silversides of the genus Labidesthes (Atheriniformes: Atherinopsidae) - Werneke, David C.; Armbruster, Jonathan W. (Zootaxa, 2015)
The two species of Labidesthes, L. sicculus and L. vanhyningi, are herein redescribed. Labidesthes sicculus is separated from L. vanhyningi by the presence of an anterolateral process of the post temporal that is longer than it is wide (versus wider than long), a ratio of thoracic length to abdominal length greater than two (versus less than two), and a midlateral stripe that is narrows in front of first dorsal fin (versus expanding in front of first dorsal fin). Labidesthes sicculus is found in Gulf of Mexico drainages from the Brazos River East to the Pascagoula River, Mississippi River (absent in middle and upper Missouri River), and Great Lakes-St. Lawrence River (absent in Lake Superior). Labidesthes vanhyningi is found in Gulf Mexico drainages from the Neches River East around peninsular Florida North on the Atlantic Coast to the Pee Dee River, in the Mississippi River it is confined to lowland areas of the Lower Mississippi River.